Noise reduction in the spectral domain of hyperspectral images using denoising autoencoder methods - Zhang, Chu; Zhou, Lei; Zhao, Yiying; Zhu, Susu; Liu, Fei; He, Yong (Chemometrics and intelligent laboratory systems, 2020)
Denoising of spectra has been a great challenge in hyperspectral image analysis. Near-infrared hyperspectral images of milk powder, rice flour and soybean flour were acquired and denoising in the spectral domain were studied. Noise free spectra and noises were simulated based on sample pixel-wise spectra. The noisy spectra with signal to noise ratio (SNR) around 45 ​dB (similar to real pixel-wise spectra) were simulated. The simulated noisy spectra were preprocessed by traditional methods as moving average smoothing (MAS), Savitzky-Golay smoothing (SGS), wavelet transform (WT) and empirical mode decomposition (EMD). The basic denoising autoencoder (DAE-1) and the stacked DAE (DAE-2) were studied for denoising. The noisy spectra with SNR around 35 ​dB and 55 ​dB were further simulated to explore the effectiveness of DAE based methods. DAE-1 and DAE-2 performed better than the other methods, with higher SNR, lower mean squared error (MSE) and mean absolute error (MAE). The developed DAE methods were applied to real-world pixel-wise spectra with good performances. The overall results proved the feasibility of using DAE based methods for noise reduction in the spectral domain of hyperspectral images, and the DAE based methods have great potential to be extended to spectral denoising of other vibrational spectroscopy techniques. •Denoising autoencoder based methods were used for pixel-wise spectra denoising.•Noise-free spectra and noises were simulated by real-world pixel-wise spectra.•Four different conventional spectral denoising methods were used for comparison.•Real-world pixel-wise spectra denoising was conducted using the developed methods.